2021
DOI: 10.1091/mbc.e21-04-0219
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of ubiquitin and CHMP5 with the V domain of HD-PTP reveals role for regulation of Vps4 ATPase

Abstract: The family of Bro1 proteins coordinates the activity of the Endosomal Sorting Complexes Required for Transport (ESCRTs) to mediate a number of membrane remodeling events. These events culminate in membrane scission catalyzed by ESCRT-III, whose polymerization and disassembly is controlled by the AAA-ATPase, Vps4. Bro1-family members Alix and HD-PTP as well as yeast Bro1 have a central ‘V’ domains that non-covalently bind Ub and connect ubiquitinated proteins to ESCRT-driven functions such as the incorporation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…Although a role in eHAV release remains to be studied, NEDD4-family E3 ligases like ITCH are involved in the budding of many conventional enveloped viruses, including HIV-1 [47, 61, 62]. Ubiquitylation is a common signal for cargo to be trafficked into MVE, and the V domains of both ALIX and HD-PTP have specific ubiquitin-binding activities [42, 63, 64].…”
Section: Discussionmentioning
confidence: 99%
“…Although a role in eHAV release remains to be studied, NEDD4-family E3 ligases like ITCH are involved in the budding of many conventional enveloped viruses, including HIV-1 [47, 61, 62]. Ubiquitylation is a common signal for cargo to be trafficked into MVE, and the V domains of both ALIX and HD-PTP have specific ubiquitin-binding activities [42, 63, 64].…”
Section: Discussionmentioning
confidence: 99%
“…V domain Proline Rich Region (PRR) ALIX LBPA, [77] CHMP4 [78] Ub, [22] GAG, [19] Syntenin, [18] AMSH3 [15] TSG101, [19,78] CEP55, [79] ALG2 [80] HD-PTP STAM2, CHMP4 [81] UBAP1, [82] VPS4, Spastin, Rps6KC1, SNX15, Ub, CHMP5, [5] UBPY [16] TSG101 [81] Bro1 Snf7 [83] Vps4, [13] Rfu1, [84] Ub, Vps60 [4] Doa4, [14] Vps23, [85] Rsp5 [85] Vps23/TSG101 as well as de-ubiquitinating enzymes such as Doa4, AMSH3, and UBPY, and the Ub-ligase Rsp5 (Table 1). [1,[14][15][16][17][18][19] Recruitment of Doa4 to the site of MVB cargo via Bro1 recycles Ub to escape degradation in the lysosome/vacuole, [14] and its association with the HECT Ub ligase Rsp5 may help reinforce cargo ubiquitination in a manner akin to that proposed for other Ub-cargo receptors.…”
Section: Bro One Domain (Bod)mentioning
confidence: 99%
“…[20] Bro1 is also an endosomal Ub-sorting receptor, that operates in parallel with other ESCRT-mediated Ub-cargo sorting pathways. [4,6] ALIX and HD-PTP harness ESCRT function during viral budding and MVB sorting in mammalian cells and bind Ub via their V domains, [5,7,19,21,22] yet the full physiological role that Ub-binding fulfills is likely incompletely understood. Recent work has shown that V domains of Bro1 and HD-PTP stimulate Vps4 ATPase activity and do so in a manner that is enhanced when those V domains bind Ub.…”
Section: Bro One Domain (Bod)mentioning
confidence: 99%
See 2 more Smart Citations